Tourism Opportunities in the China-Mongolia-Russia Economic Corridor - Luvsandavaajav, Oyunchimeg (Turisztikai és Vidékfejlesztési Tanulmányok, 2022)
The development of an economic corridor enhances regional cooperation through attracting investments, creating a transport network, information, and communication technology, providing job opportunities, linking urban and rural areas, and developing tourism. This study aims to review the opportunities for tourism corridor development based on the rail and road transport corridor between China, Mongolia, and Russia. Strengthening tourism cooperation in the economic corridor between three countries is important yet challenging with potentials. Tourism demand, tourist facilities, amenities, challenges, threats, and opportunities in the economic corridor are examined. The result implies implications and recommendations for regional tourism development along the economic corridor among three countries with a sustainable approach to the environment, economy and culture, tourism product planning, and market policy. Furthermore, the study proposes an option for regional tourism development between three nations by linking natural and cultural attractions with tourism products, which aim to increase the number of visitors.